A Critical Assessment of the Kinetics and Mechanism of Initiation of Radical Polymerization with Commercially Available Dialkyldiazene Initiators. (January 2019) - Moad, Graeme
Graphical abstract: The dialkyldiazenes are one of the most important classes of initiator used in both conventional and reversible deactivation radical polymerization (RDRP). This paper summarizes the current state of knowledge of mechanism of radical generation and provides a critical assessment decomposition rate constants ( k d ) and efficiencies ( f ) of commercially available initiators. Abstract: The dialkyldiazene or azo-compound initiators, which include azonitriles such as azobis(isobutyronitrile) (AIBN), are one of the most important classes of initiator being widely used in both conventional and reversible-deactivation radical polymerization (RDRP). This paper briefly reviews the mechanism of radical generation from dialkyldiazenes and provides a critical assessment and recommended values for the decomposition rate coefficients ( k d ) and efficiencies ( f ) of those that are commercially available. A critique of the methods that have been used for the determination of these kinetic parameters is also provided. In this review, a focus is placed on initiation of radical polymerization of the more reactive monomers such as methyl methacrylate (MMA) and styrene at low monomer conversions; where addition of the initiator-derived radicals to monomer is not rate determining (i.e., k i > k p ) and, thus, the efficiencies for radical generation ( f g ) and for initiation of polymerization ( f i ) are similar. However, the dependence of the kinetic parameters on such factors as monomer type, monomer conversion, reaction medium, temperature, photo-irradiation, microwave irradiation and magnetic fields is also discussed. We additionally provide comment on the use of dialkyldiazenes in heterogeneous polymerization (emulsion or dispersion polymerization) and in RDRP. Dialkyldiazenes are the most used initiators in RAFT (reversible addition-fragmentation chain-transfer) polymerization and other RDRP based on degenerative chain transfer, which include iodine transfer polymerization (ITP) and tellurium-mediated polymerization (TERP). They also find significant use in various forms of stable-radical-mediated radical polymerization (SRMP), in particular nitroxide-mediated polymerization (NMP) and cobalt-mediated radical polymerization (CMRP), and have an integral role in certain atom-transfer radical polymerization (ATRP) processes, such as reverse and ICAR (initiators for continuous activator regeneration) ATRP and variations on these procedures. In each of these RDRP methods, knowledge of the parameters that characterize the kinetics and efficiency of dialkyldiazene decomposition and the mechanism of initiation is beneficial to understanding and for optimizing control over the process.